Tranquility (Tuma’ninah) Amid Crisis: The Concept of Mental Health and Resilience from the Perspective of Tafsir Al-Munir - Farhah Farhah; Safrudin Edi Wibowo; Khoirul Faizin (Eastasouth Institute, 2026)
The phenomenon of mental health, especially among the younger generation, is characterized by many modern people experiencing emotional disorders, high rates of anxiety, depression, and so on, triggered by exposure to social media, economic uncertainty, and environmental pressures. The Qur'an, as a source of law, also serves as a guide for Muslims in overcoming life's problems, including mental health. This study aims to: 1) Describe the concept of mental health in al-Munir's interpretation, 2) Describe efforts to manifest mental health in al-Munir's interpretation, 3) Determine the relevance of mental health applications in al-Munir's interpretation and contemporary anxieties of modern society. This study uses a descriptive qualitative method with a literature review type of research. The research data sources were obtained from various primary and secondary data sources, namely books, literature, reports, and other documentation materials that are relevant to the research. The results of the study show that 1) The concept of mental health contained in al-Munir's interpretation includes behaviors and attitudes that are ingrained in a person's mind, which are manifested in the form of happiness, calm, and peace of mind, 2) Efforts to manifest mental health in the interpretation of al-Munir can be realized through patience when overcoming life's difficulties, happiness, calm and relaxation, as well as healing the soul, 3). The applicable relevance of mental health in the interpretation of al-Munir and contemporary anxiety of modern society can be imprinted from mental health problems which include anxiety disorders, stress, depression and so on which have occurred a lot and cannot be considered trivial, this matter requires an approach to Allah SWT so that it can achieve ketuma'ninahan in life.